2019
DOI: 10.1038/s41598-019-51576-0
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of a virulent Streptococcus suis serotype 9 lineage distinguishable from carriage subpopulations

Abstract: Streptococcus suis is a porcine pathogen, causing severe invasive infections. S. suis serotype 9 is increasingly causing disease in Dutch and Chinese pig herds, but it is unknown whether all serotype 9 isolates are equally virulent and markers that can identify virulent strains are not available. Therefore, discrimination between virulent isolates and carriage isolates typically not associated with disease, is currently not possible. We collected tonsillar S. suis isolates from 6 herds not previously diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…A systematic analysis of the data showed that the clinical isolates clustered mainly together in one group whereas the carriage isolates were distributed across 8 different groups. This suggested that virulent serotype 9 isolates are genetically very similar, whereas the carriage isolates are more heterogeneous [8], as was described before [10,64,79,84]. Based on our data, the heterogeneity was only found for the carriage isolates.…”
Section: A2 Population Genetics Of S Suis Serotypesupporting
confidence: 82%
See 2 more Smart Citations
“…A systematic analysis of the data showed that the clinical isolates clustered mainly together in one group whereas the carriage isolates were distributed across 8 different groups. This suggested that virulent serotype 9 isolates are genetically very similar, whereas the carriage isolates are more heterogeneous [8], as was described before [10,64,79,84]. Based on our data, the heterogeneity was only found for the carriage isolates.…”
Section: A2 Population Genetics Of S Suis Serotypesupporting
confidence: 82%
“…Nevertheless, other serotypes are increasing in importance in different countries, as is the case of serotype 9, particularly in some countries of Western Europe. By means of novel animal models and diagnostic tools, de Greeff et al (Appendix A) epidemiologically determined the population genetics of S. suis serotype 9 in The Netherlands [8]. Obtained data using comparative genome hybridization and whole genome sequencing suggest that clinical serotype 9 swine isolates are genetically very similar whereas serotype 9 isolates carried by healthy pigs are more heterogeneous.…”
Section: Diagnosis and Epidemiology Of The S Suis Infection In Humans And Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has also highlighted the diversity of serotype 9 in Chinese S. suis isolates [11]. Furthermore, a collection of serotype 9 isolates in the Netherlands was shown to contain some strains with the ability to cause severe disease and others only inducing mild clinical signs which was confirmed in experimental infection of piglets [12]. Virulent serotype 2 strains in Europe generally carry the genes epf, mrp and sly encoding the extracellular factor, the muramidase-released protein and the hemolysin suilysin, respectively [8,9,13].…”
Section: Introductionmentioning
confidence: 87%
“…The bacterial virulence-associated factors may be classified into the following sub-groups (of note, some genes probably may be classified into more than one categories due to their dual characteristics): (i) surface/secreted elements; (ii) protease enzymes; (iii) transcription factors/regulatory systems and (iv) other virulence determinants (transporters/secretion systems) [ 18 ]. The list of confirmed and putative virulence factors is extensive, but the most prominent and best-characterized virulence factors of clinical S. suis strains are surface and secreted elements: capsular polysaccharides, extracellular factor (EF; epf ), muramidase-released protein (MRP; mrp ) and a 38-kDa surface protein, suilysin (SLY) [ 19 , 20 , 21 , 22 ]. S. suis isolates are included a complex population consisting of heterogeneous strains and they may be classified into 35 serotypes (1–34, 1/2) to date, based on the principal virulence factor, the capsular polysaccharide antigen (CPS) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%